1994
DOI: 10.1002/ijc.2910590314
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the FGFR1 gene in human breast‐carcinoma cells

Abstract: Fibroblast growth factors (FGF) constitute a family of at least 9 members which act through high-affinity tyrosine-kinase receptors encoded by 4 distinct genes. In humans, the FGFR1 gene is located in chromosomal region 8p12. Its amplification and expression were examined in a panel of 110 breast carcinoma samples by Southern- and Northern-blot analyses. FGFR1 was amplified in 9% and overexpressed in about 15% of the tumors studied. In situ hybridization experiments were performed on tissue sections of normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
39
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 25 publications
2
39
2
Order By: Relevance
“…Other cell lines tested express low to moderate level of one or more of the four FGF receptors. However, the results obtained with crosslinking studies did not always so extensively correlate with published work using either RNA (Jacquemier et al, 1994;Penault-Llorca et al, 1995, but see also McLeskey et al, 1994 or Western blot studies (Luqmani et al, 1995). For instance, FGFR1 and FGFR2 RNA expression was found negative in respectively 1 (MDA-MB-453) and 4 (MDA-MB-134, BT 474, ZR 75-1 and MDA-MB-453) cell lines where we detected surface expression of the receptor.…”
contrasting
confidence: 64%
See 2 more Smart Citations
“…Other cell lines tested express low to moderate level of one or more of the four FGF receptors. However, the results obtained with crosslinking studies did not always so extensively correlate with published work using either RNA (Jacquemier et al, 1994;Penault-Llorca et al, 1995, but see also McLeskey et al, 1994 or Western blot studies (Luqmani et al, 1995). For instance, FGFR1 and FGFR2 RNA expression was found negative in respectively 1 (MDA-MB-453) and 4 (MDA-MB-134, BT 474, ZR 75-1 and MDA-MB-453) cell lines where we detected surface expression of the receptor.…”
contrasting
confidence: 64%
“…Ampli®cation of FGFR genes are well documented in human tumours Zhou et al, 1988;Theillet et al, 1989;Ade laõÈ de et al, 1988;Birnbaum et al, 1991), and overexpression of FGFR1, FGFR2 and FGFR4, but not FGFR3, messenger RNA has been described in human breast cancers (Jacquemier et al, 1994;Penault-Llorca et al, 1995;Luqmani et al, 1995) suggesting a role for these receptors in tumour development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated the presence of FGFR1 and FGFR2 mRNA in both normal and breast cancer samples as well as a panel of breast cell lines and normal human tissues (Luqmani et al, 1992a), and Jacquemier et al (1994) have also demonstrated the presence of FGFR1 mRNA in normal and malignant breast epithelial cells using in situ hybridization. Since then we have shown that breast cancer tissues and cell lines express a preponderance of mRNA and protein for the two-loop variant form of FGFR1 as opposed to the full-length three-loop form .…”
mentioning
confidence: 77%
“…About 10% of breast cancers have been shown to contain amplified levels of the genes for FGFR1 (Adnane et al, 1991;Jacquemier et al, 1994) and FGFR4 (Jaakkola et al, 1993). Jacquemier et al (1994) also reported overexpression of FGFR1 mRNA in 14.5% of breast tumours and Penault-Llorca et al (1995) found both FGFR1 and FGFR4 mRNA to be expressed at high levels in 22% and 32% of breast cancers respectively.…”
Section: Discussionmentioning
confidence: 99%